CONNECTING EDUCATION AND INFORMATION: A NEW ERA UNDER NEP 2020 - Pusadkar, Ankit V.; Fating, Purvesh P. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The National Education Policy (NEP) 2020 introduces strategies to modify Indian education systems by targeting accessibility improvements and maintaining equity and enhancing quality outcomes. In this evolving framework libraries function as centers of learning while serving as knowledge repositories to establish essential connections between education and information. This paper examines NEP 2020’s evolving library expectations through an analysis of multidisciplinary teaching methods and digital education initiatives and continuing education strategies. macenagers enable innovation through their capacity to merge digital technologies with traditional resources and develop accessible learning environments which support students from all backgrounds while providing equal information access. The research explores financing barriers alongside missing digital infrastructure and inadequate skills of information professionals in libraries. Through case studies and best practices the paper delivers effective recommendations for NEP 2020 implementation and helps policymakers alongside educators and librarians achieve alignment in service design. The research demonstrates how libraries function as critical infrastructure which enables knowledge distribution and critical thinking capabilities to create a society built on education and empowerment.